PENGEMBANGAN MEDIA ILUSTRASI DA LA M MATERI KENNENLERNEN PADA KETERAMPILAN MEMBACA SISWA KELAS X SMAN 12 SURABAYA - Hartha, Bagas; Samsul, Samsul Imam (LATERNE, 2021)
Students' understanding is derived from the acceptance of the material presented by the teacher. The acceptance of materialsby students delivered relies on listening and reading skills. Therefore, it is important to improve both skills, especiallyreading. According to the german language subject teacher at SMAN 12 Surabaya, there are difficulties about the exposure ofkennenlernen material along with German grammatics regarding verben conjugation and case ( Fall). The focus of Germanlanguage learning at high school level is limited to reading ability. This focus is felt precisely with the media developed. This isbecause the image is dominant but still supports the text that will be by the students. With this media it is expected that in thisdevelopment research learning will be more interesting and students will more easily master vocabulary. The method used is thedevelopment of Research and Develompent (R& D) theory of Borg and Gall. The research measures include: (1) analyze,(2) design, (3) development, (4) implementation, and (5) evaluation. This research missed the implementation stage due tothe Covid-19 pandemic outbreak, so that after the development stage immediately switched to the evaluation stage, namely byconducting validation tests on material experts I, material experts II and media experts. The results of the analysis concluded thatthe development of Board Game media has been feasible to use. This is indicated by the validation results conducted by 3 experts,namely 1 media expert and 2 material experts. Validation results conducted by material experts and media experts showed values of79%, 83% and values of 97.3% so that it is generally categorized as strong so that it can be used without revision. Kata Kunci: development, illustration, reading skills